Monitoring Successional Changes in Pasture Phytocenoses in 'Exhausted' Areas of Deflation in the North-West Caspian Region - L. P. Rybashlykova; A. I. Belyaev; A. M. Pugacheva (Юг России: экология, развитие, 2020)
Aim. The main objective of the research was to study the processes of regeneration and dynamic development of the modern vegetation cover of pastures previously differently phytomeliorated. Successions of the natural dynamics of vegetation of regenerated pastures of the north-west Caspian region (in the period 2014-2018) were considered.Material and Methods. A study of the vegetation cover was carried out during geobotanical surveys using the test site method. Description of vegetation was carried out according to the Brown-Blanca technique.Results. Analysis of the succession dynamics showed that after phyto-forest reclamation and relief stabilisation, deflation foci begin to overgrow from the very first year. Regeneration of the steppe vegetation in forest-reclaimed deflated pastures -if fires do not occur - proceeds quickly and naturally. The creation of forest pastures in the stabilization of open sands shortens the time required to halt sand transfer, accelerates the first stages of overgrowth by psammophytic plants and zonal pasture vegetation appears earlier than with phytomelioration with only grasses and the natural overgrowth of degraded arid pasture ecosystems following the reduction or absence of anthropogenic load.Conclusions. The modern species composition and structure of plant communities in the areas studied suggest that consecutive successions are occurring and that communities have formed that are close in species composition to the zonal - confined to brown desert-steppe solonetzic sandy and loamy soils dominated by cereals and wormwood. Projective coverage is up to 80%.